IMPLEMENTASI PENDIDIKAN KARAKTER PADA KURIKULUM ISMUBA SD MUHAMMADIYAH KALISOKA SENTOLO KULONPROGO DIY - Tito Restu Tantowi; Hendro Widodo (Universitas Muhammadiyah Ponorogo, 2019)
Curriculum as one of the important components in achieving educational goals in school. No exception in the Muhammadiyah school, which has a curriculum from the primary and secondary education board of the Muhammadiyah central leadership, must also be adapted to the government in Kulon Progo district. Therefore SD Muhammadiyah Kalisoka developed the ISMUBA curriculum but also implemented regulations to strengthen character education.Objective: To know the implementation of regulations on strengthening character education in Muhammadiyah KalisokaMethod: Field research at SD Muhammadiyah Kalisoka, Tuksono, Sentolo, Kulon ProgoResults: The regulation on strengthening character education has been inputted in developing the Islamic curriculum at Muhammadiyah Elementary School KalisokaConclusion: From the results of the study it was found that Muhammadiyah Kalisoka Elementary School had succeeded in developing regional regulations to strengthen character education in its ISMUBA curriculum and had met the achievement indicators.